2017
DOI: 10.1136/bmj.j2497
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of risk prediction equations to estimate survival in patients with colorectal cancer: cohort study

Abstract: Objective To develop and externally validate risk prediction equations to estimate absolute and conditional survival in patients with colorectal cancer. Design Cohort study. Setting General practices in England providing data for the QResearch database linked to the national cancer registry. Participants 44 145 patients aged 15-99 with colorectal cancer from 947 practices to derive the equations. The equations were validated in 15 214 patients with colorectal cancer from 305 different QResearch practices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 45 publications
6
57
1
2
Order By: Relevance
“…Similar results were reported in a study from Ontario, Canada, while another study showed improved survival associated with ACT regardless of high‐risk features . Moreover, a recent large cohort study from England reported an increased risk of colorectal cancer death and no significant risk of death from other causes for Stage II patients receiving ACT . We observed ACT administration to be associated with higher survival in total Stage II patients in Sweden, and in high‐risk Stage II patients in all countries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported in a study from Ontario, Canada, while another study showed improved survival associated with ACT regardless of high‐risk features . Moreover, a recent large cohort study from England reported an increased risk of colorectal cancer death and no significant risk of death from other causes for Stage II patients receiving ACT . We observed ACT administration to be associated with higher survival in total Stage II patients in Sweden, and in high‐risk Stage II patients in all countries.…”
Section: Discussionsupporting
confidence: 90%
“…34 Moreover, a recent large cohort study from England reported an increased risk of colorectal cancer death and no significant risk of death from other causes for Stage II patients receiving ACT. 35 We observed ACT administration to be associated with higher survival in total Stage II patients in Sweden, and in high-risk Stage II patients in all countries. These patterns may support suggestions that the association of ACT with higher survival of high-risk Stage II patients seen in observational studies are primarily related to patient selection rather than reflect the direct benefit from ACT.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 62%
“…Az egyéb okból bekövet-kező mortalitás eredménye alapján a szerzőkben felmerült a kérdés, hogy a betegek alacsonyabb túlélését a T2DM a tumoros betegséggel való kapcsolata miatt rontja-e, vagy valamilyen egyéb, a T2DM-mel kapcsolatos komorbiditás alakult-e ki a háttérben. Hippisley-Cox és munkacsoportja [50] a női és férfi CRC-betegeket kü-lön-külön vizsgálta abból a szempontból, hogy a T2DM milyen szerepet játszik a betegek túlélésében. Mindkét nem esetén rövidebb túlélési időket igazoltak T2DM jelenlétében (nők: esélyhányados: 1,12; 95%-os KI 1,02-1,23; férfiak: esélyhányados: 1,14; 95%-os KI 1,05-1,24), mint a nem T2DM-személyeknél.…”
Section: Megbeszélésunclassified
“…Mindkét nem esetén rövidebb túlélési időket igazoltak T2DM jelenlétében (nők: esélyhányados: 1,12; 95%-os KI 1,02-1,23; férfiak: esélyhányados: 1,14; 95%-os KI 1,05-1,24), mint a nem T2DM-személyeknél. Li [49], illetve Hippisley-Cox [50] munkacsoportjának eredményét, a T2DM-et mint önálló, a túlélést befolyásoló tényezőt saját vizsgálati csoportunkban nem tudtuk alátámasztani, de ez a minta méretével is összefüggésben lehet.…”
Section: Megbeszélésunclassified
“…16 Many predictors of survival among CRC patients have been identified; these may assist patients and healthcare personnel in decision making and disease management. 12 However, few previous studies have looked at the influence of T2D status in different ethnic groups. Given the high T2D incidence in many non-white populations 17 and the elevated CRC incidence in Japanese and African Americans 18 , it is of interest to identify ethnic-specific differences in the association to understand differences in prognosis.…”
Section: Introductionmentioning
confidence: 99%